Pengaruh Lamanya Perendaman Terhadap Absorpsi, Ketahanan Aus, dan Kuat Tekan Paving Block - Wajdi, Bina Arumbinang; Mudiyono, Rachmat; Soedarsono, Soedarsono (UM Purwokerto Press, 2023)
Paving blocks are considered advantageous over other road surfaces, and it is undeniable that paving blocks are an alternative road surface whose quality is still affected by water flooding. The objective of this study was to determine the effects of soaking time and age of paving blocks in terms of absorption, wear resistance, and compressive strength. The paving blocks used were manual (Holland) brick models obtained from Banyubiru and mechanical ones obtained from PT Pohon Cemara Semarang. The variations soaking times were 0, 12, 24, 36, 48 (hours) for 7, 14, 21, 28 (days) old pavers. The tests conducted were absorption, wear resistance, and compressive strength tests of paving blocks, carried out in the UNISSULA civil engineering laboratory. The results of absorption tests manual and machine paving block showed that value of the absorption test increased with increasing soaking time. The results of wear resistance of manual and machine pavers show that the untreated samples had a lower wear value and all test results met the requirements of SNI 03-0361-1996 Quality A. The maximum compressive strength of manual paving blocks at 28 days of age without treatment is 13.334 MPa. The maximum compressive strength of machine-made pavers is 25.297 MPa for paving blocks without immersion.